A one-day training on the FABLE Calculator at FAO - Chemarin, Charlotte; Aline, Mosnier; Clara, Douzal (2024)
On May 28th, upon the initiative of the Director of Agrifood Economics Division (ESA), David Laborde, and the Chief Economist, Maximo Torero, the FABLE secretariat organized a one-day training on the FABLE Calculator for 33 staff members coming from 9 FAO divisions.